The Relationship between the Mean Platelet Volume and Subacromial Impingement Syndrome - Yalkın Çalık; Ayça Filiz Çalık (Galenos Yayinevi, 2015)
Objective: Subacromial impingement syndrome (SIS) characterized by inflammation of supraspinatus tendon is one of the most common causes of the shoulder pain. In some studies, platelet activity has been shown as a marker to indicate the inflammation associated with the disease. The mean platelet volume (MPV) shows platelet function and activation. The aim of this study was to investigate the relationship between MPV and SIS. Materials and Methods: Eighty seven inpatients (female/male: 55/32, mean age: 56.34±7.53 years) diagnosed with SIS according to physical examination and MR findings in Bolu Physical Therapy and Rehabilitation Hospital between January 2014- June 2014 constituted the case group, 87 outpatients (female/male 61/26, mean age: 52.97±8.48 years) not diagnosed with SIS constituted the control group. MPV values between case and control group that were similar in terms of age and gender were compared. Results: In case group MPV (8.36±0.73***) was lower than that of the control group (8.44±1.02****) and platelet count (253.75±50.17***) was higher than that of the control group (244.79±56.19***). Both were not statistically significant (p>0.05). Significant negative correlation was found between MPV and platelet level in case group (r=-0.240, p<0.05). Conclusion: These findings present that there is no relationship between MPV and SIS. New prospective studies are needed on this subject. (Turkish Journal of Osteoporosis 2015;21: 15-8)